PENENTUAN STRATEGI KEUNGGULAN BERSAING DALAM MENINGKATKAN PENDAPATAN DI MASA NEW NORMAL PADA UKM TAHU SUSU DESA BADAS KECAMATAN SUMOBITO KABUPATEN JOMBANG - Dina Eka Shofiana; Abid datul Mukhoyaroh; Iin Uzlifatul Khoiroh (Prosiding Conference on Research and Community Services, 2021)
The community realizes the importance of having a business in the Covid-19 era after being laid off by the company. Thus, UKM (Usaha Kecil Menengah) are the hopeness of the community to accelerate economic growth, one of which is UKM tahu susu in Badas village is increased in income during Covid-19 era.This study aims to make UKM tahu susu in Badas village able to maintain sales of milk tofu to increase income, and to improve their business by creating new strategies that will satisfy customers. In order to UKM tahu susu still provide good results by selling their product in the new normal era. The method used in this study is a qualitative research with the tecnique of data collections namely observations, interviews, documentation. Furthermore, it determine the author's competitive advantage using SWOT analysis, IFAS, and EFAS. From the results of the combination of these two factors, it can be concluded that the determination of a competitive advantage strategy for UKM tahu susu was that SO (supports the growth strategy) in accordance with the company's way of marketing plan, namely by avoiding threats to other UKM tahu susu. Thus, the strategies that could be done such as (1) Maintaining Product Quality (2) Conducting Targeted Promotions (3) Maintaining Relationships With Consumers (4) Maintaining Prices In A Profitable Position. Then, the using of a Cartesian diagram to determine the position of UKM tahu susu. Thus, the position of UKM tahu susu in Badas village from the SWOT analysis was in quadrant II, which was a good product, but many threats namely the versification of quadrant, while in the IFAS and EFAS analysis they were in quadrant IV, namely weak products but there were opportunities that could be used, called quadrants turn around.